ANALISIS STRUKTUR, PERILAKU, DAN KINERJA PASAR KOMODITI PADI DI KOTA LANGSA - Putri Ogy Mawarni; Muslimah Muslimah; Fiddini Alham (Journal of Innovation Research and Knowledge, 2023)
Methods (1) Structural Analysis (2) Behavioral Analysis (3) Performance Analysis. The results of data analysis obtained the following results: The market structure formed in the rice market in Langsa City at the farmer level leads to a loose oligopoly market. And at the level of marketing agencies shows a tight oligopoly market. The behavior of the rice market in Langsa City can be seen that (1) at the farmer level with a loose oligopoly market structure that is formed, farmers have a low bargaining position and only act as price takers. (2) market behavior in rice marketing institutions in Langsa City as a tight oligopoly market.. The market performance of the Rice Commodity in Langsa City has a share price at the farmer level, namely 45% and 160%. The value of the price share of marketing institutions in the marketing channel group I is 88% for refineries, 50% for collectors and 100% for retailers. Meanwhile, in the marketing agency marketing channel group II, namely refineries 123.07% and retailers 100%. At each marketing agency in all groups of marketing channels the R/C ratio value is more than 1, so that rice marketing carried out by marketing agencies is feasible.